IMPLEMENTATION OF AN EXTERNAL QUALITY ASSURANCE SYSTEM IN SMP PLUS MIFTAHUL HIDAYAH AL-SYAFA - Nurmalasari, Neneng (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
This research aims to find out how the external quality assurance system is implemented at SMP Plus Miftahul Hidayah Al-Syafa. This research uses a descriptive qualitative approach. The data collection technique is triangulation. Data analysis is inductive, external quality assurance is detailed and accurate through data results derived from written data and documentation as well as oral interviews with related people. The results of the information found are that the implementation of an external quality assurance system is important for every educational unit. This is done to create the quality of education as expected. The implementation of external quality assurance at SMP Plus Miftahul Hidayah Al-Syafa can be categorized as quite good, namely graduate competency standards, curriculum content standards, process standards, teacher and teaching staff standards, facilities and infrastructure standards, teaching unit management standards, financing standards and assessment standards.